Analisis Pelaksanaan Asesmen Nasional Berbasis Komputer Tahun Ajaran 2024/2025 dalam Meningkatkan Mutu Pendidikan di SDN Kawungsari - Endang Solihah; Ani Nur Aeni; Isrokatun Isrokatun (Mathematics Education Study Program, 2025)
Computer-based National Assessment (ANBK) is an evaluation tool that replaces the national exam which aims to map the quality of education in each education unit at the primary and secondary levels carried out with the CAT (Computerized Adaptive Testing) system. The purpose of this study is to analyze and describe the implementation of ANBK as a way to improve the quality of sustainable education. This research method is a case study with a qualitative approach. The data collection techniques used were interviews, observation and documentation. The research findings obtained are that the implementation of ANBK at SDN Kawungsari is carried out in an online mode with two sessions, there are obstacles in the form of inadequate facilities, server down, unstable network and there are still some students who are not fluent in reading and the ANBK results have improved 5 out of 6 assessment indicators. Based on these findings, it can be concluded that the implementation of ANBK at SDN Kawungsari went well, there were technical and non-technical obstacles, and the ANBK results obtained showed an increase from the previous year, which means that the quality of education at SDN Kawungsari is also better.